①若m+n=6,mn=8,则mn²+m²n=?②若x²-mx+n能分解因式为(x+2)(x-5),则m+n=?

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/19 20:44:14
①若m+n=6,mn=8,则mn²+m²n=?②若x²-mx+n能分解因式为(x+2)(x-5),则m+n=?
xő0_-j7MI@={ 'N6MjA #*"倸/Ļ,M魯ӴCd3_3t|&4I픣B^j&[҃J6s] 4|=]~PNej~uUZ*m~pjȺn]i'dKw^bb2U-nrnnµd1οI ;V9I]:=^{3?{xv5{[~>. Ϙnꯓá:kD+툵 ]Px!)oUԊcULRVt lmcyNm7QHI] 14Kz^n,'$&{BP} BdA"1y 䱅M =ײ qCrϋlbJt!ˮX-KHIpNB+\0

①若m+n=6,mn=8,则mn²+m²n=?②若x²-mx+n能分解因式为(x+2)(x-5),则m+n=?
①若m+n=6,mn=8,则mn²+m²n=?
②若x²-mx+n能分解因式为(x+2)(x-5),则m+n=?

①若m+n=6,mn=8,则mn²+m²n=?②若x²-mx+n能分解因式为(x+2)(x-5),则m+n=?
①若m+n=6,mn=8
则mn²+m²n=mn(m+n)=8*6=48
②若x²-mx+n能分解因式为(x+2)(x-5)
因为(x+2)(x-5)=x²-3x-10
所以m=3,n=-10
则m+n=3-10=-7
如果不懂,祝学习愉快!

  1.mn²+m²n=mn(m+n)=48
  2. -m=-5+2=-3,n=2*(-5)=-10;
  m+n=-7